Optimalisasi Branding Produk Melalui Inovasi Kemasan Pada UMKM Kerupuk Ibu Ramlah Desa Rabakodo Kabupaten Bima - Purnama, Ita; Nurhaliza, Ana; Mutmainah, Mutmainah (CV. Devi Tara Innovations, 2025)
This study aims to optimize the product branding strategy of Kerupuk Ibu Ramlah UMKM through packaging innovation. In the context of tight market competition and the important role of UMKM in the Indonesian economy, effective branding is the key to competitiveness. Packaging innovation not only functions as a product protector, but also as a visual communication media to attract consumer interest. This study uses direct survey methods, interviews, and an implementation approach that includes the preparation, implementation, and evaluation stages. The results of the study showed a significant increase in consumer interest, product durability, and sales profit after the implementation of new packaging. These findings prove that packaging innovation is an effective branding strategy to improve the competitiveness and image of UMKM products. This study is expected to be a practical reference for other UMKM in developing branding strategies based on innovative packaging.